Development of a Smart Laboratory Iot Trainer Kit Based on Raspberry Pi with The Addition of Fire Sensor, Gas Sensor, and RFID and Monitor Screens in The Telecommunications Lab of The Faculty of Engineering Unesa - Oka Kusuma, Hikmat; Sudarto, Gitut (Proceeding of International Joint Conference on UNESA, 2024)
Integrating IoT concepts into education is critical, and the creation of intelligent IoT lab trainers plays a vital role in this process. This paper outlines the creation of a sophisticated laboratory IoT Trainer kit utilizing a Raspberry Pi. The Telecommunications Lab of Surabaya State University’s Faculty of Engineering has fire and gas sensors, RFID technology, and monitoring screens. This trainer facilitates remote monitoring and control of network-connected equipment. The Raspberry Pi microcontroller offers automatic tracking and fast response to potential hazards such as fire or gas leaks by combining computer vision-based sensors and gas/fire detectors. This technique uses a research and development (R&D) structure which includes planning, development, evaluation, and improvement stages. Hardware design, sensor integration, power management, and testing processes are crucial. This prototype is an interactive educational tool fostering comprehension of IoT concepts among students and consumers. Integrating with the Telegram Bot API makes it possible to actively monitor and receive real-time notifications, thereby enhancing laboratory security and efficiency. The successful development of this Trainer improves the standard of IoT teaching and practical training in the academic setting.